Hospitalizations for COPD Exacerbations: Trends and Determinants of Death. (2nd November 2015) - Molinari, Nicolas; Briand, Camille; Vachier, Isabelle; Malafaye, Nicolas; Aubas, Pierre; Georgescu, Vera; Roche, Nicolas; Chanez, Pascal; Bourdin, Arnaud
Abstract: Objectives: to understand epidemiological trends in severe COPD exacerbations through analyzes of hospitalizations and deaths during three consecutive years in a French administrative region area. Methods: Medico-administrative records of hospitalizations for COPD exacerbations were sorted from 2010 to 2012 using selected International Classification of Diseases (ICD10) codes. Four groups of hospitalization for COPD severe exacerbations were elicited leading to hospitalizations (general ward without respiratory failure, general ward with acute respiratory distress, ICU without mechanical ventilation, ICU with mechanical ventilation). Results: Data extraction identified 5007, 4986 and 5359 admissions related to 4136, 4155 and 4460 patients in 2010, 2011 and 2012, respectively. Marked seasonal variations were observed. Duration of stay (median (IQR), 7 (7) vs 9 (8) vs 10 (9) vs 14 (16) days, P < .001), death rates (3.6% vs 14.2% vs 14.4% vs 21.2%, P < .01), number of co-morbid conditions (median (IQR), 2 (2) vs 2 (2) vs 4 (5) vs 4 (4.5), P < .01), type of institution (64.9% in public institution vs 79.9% vs 87.8% vs 76.6%, P < .01) were significantly associated with the hospitalization group and more than 8% of admissions led to death (3% to 24%). Age, type of institution and past hospitalizations were independent risk factors for deaths. Readmissions were infrequent but mainly related to the worsening of the co-morbid conditions. Conclusion: COPD severe exacerbations are frequent and lead to an important numbers of deaths related to the severity of acute respiratory failure and the number of co-morbid conditions.